JUSTICE IN ISLAM ON GENDER ISSUES (The Study of Discourse on Polygamy Regulation in Pamekasan Regency) - Trisnawati Trisnawati (Islamuna: Jurnal Studi Islam, 2016)
The issue of gender equality has long rolling and be on the agenda in many countries, including the Islamic discussion. Many studies and thinking about these gender issues by Muslim thinkers influencing the discourse of feminism studies. Muslim thinkers view that Islam has had in common with the concept of equality brought feminism. All the rules in Islam always puts equality and justice. But feminists do not think they declare Islam demikain contradictory to the spirit of justice and equality. Finally, many of the legal texts and passages that have been governing the relationship between men and women in Islam be re-examined, disassembled and modified to suit the gender equality perspective. This article exemplifies the study of discourse regulations to legalize polygamy in Pamekasan with the intention of positioning gender issues and perspectives of polygamy in Islam as true according to the quran and hadith